Featured Cover. Issue 4 (8th March 2021) - Li, Shufeng; Zheng, Xiaojuan; Wang, Ting; Xue, Jun
Abstract : The cover image is based on the Letter to the Editor Clinical characterization of novel HSPA9 splice variant in a Chinese woman by Shufeng Li et al., https://doi.org/10.1111/cge.13910 . Abstract : The cover image is based on the Letter to the Editor Clinical characterization of novel HSPA9 splice variant in a Chinese woman by Shufeng Li et al., https://doi.org/10.1111/cge.13910 .